2018
DOI: 10.2478/subboec-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Poverty Analysis of Urban and Rural Households in South Africa

Ebenezer Toyin Megbowon

Abstract: The study profiled and compared household multidimensional poverty status and its determinants among urban and rural households in the Eastern Cape Province of South Africa, using information from a sample population of 3033 households interviewed from the Province during the General Household Survey conducted by the Statistics South Africa in 2014. Analytical techniques utilized include the recent multidimensional poverty index (MPI), descriptive statistics and Tobit regression. Findings reveal that multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
5
4
2
Order By: Relevance
“…In addition, urban dwellers are better exposed to more opportunities than their rural counterparts. This finding is consistent with those reported by Ebenezer and Abbyssinia (2018) and Megbowon (2018) on Eastern Cape province of South Africa. Comparable finding has also been documented by Trani et al (2016) It is also evident from the results that households whose residences are far from the university are more at the risk of falling into multidimensional poverty.…”
Section: Discussion Of Results On the Determinants Of Multidimensional Povertysupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, urban dwellers are better exposed to more opportunities than their rural counterparts. This finding is consistent with those reported by Ebenezer and Abbyssinia (2018) and Megbowon (2018) on Eastern Cape province of South Africa. Comparable finding has also been documented by Trani et al (2016) It is also evident from the results that households whose residences are far from the university are more at the risk of falling into multidimensional poverty.…”
Section: Discussion Of Results On the Determinants Of Multidimensional Povertysupporting
confidence: 93%
“…As a matter of fact, evidence exists to have shown the effect of location on the possibility of being multidimensionally poor. Evidence from a recent study by Megbowon (2018) on Eastern Cape province of South Africa indicates higher prevalence of multidimensional poverty in the rural than urban areas. Comparable empirical evidence has also been documented by Trani et al (2016) in their study on Afghanistan.…”
Section: Marital Statusmentioning
confidence: 99%
“…They also found that of the three dimensions they examined, health had the highest deprivation However, Amukoko had the highest dimension deprivation as education and lowest as living standards. This is in contrary to the findings by Megbowon (2018), who examined multi-dimensional poverty in the Eastern Cape Province of South Africa. The standard of living contributed the highest MPI in the area.…”
Section: Fuzzy Multi-dimensional Poverty Analysiscontrasting
confidence: 99%
“…Electricity, flooring, assets and cooking fuel indicators had relatively low index across the slums. Unlike the assertion that electricity supply was a major deprivation suffered by the slum dwellers (Ige and Nekhwevha, 2014;Megbowon, 2018), this study shows that the electricity index has a low index compared to other indicators measured. Again, the majority of the house structure with the exception of Makoko and Iwaya were constructed with cement blocks and well-floored.…”
Section: Fuzzy Multi-dimensional Poverty Analysiscontrasting
confidence: 98%
“…The most striking thing about poverty is that it has become multi-dimensional phenomenon overtime (Jung-Eun, Won-Hong, Bong, & In, 2015;Oshio & Kan, 2014). This perspective on poverty goes beyond the traditional uni-dimensional approach that primarily focuses on income or consumption expenditure (Megbowon, 2018). The justification behind this is based on the idea that income indicator is incomplete and its shortfalls lead to inaccurate estimations of poverty (Diaz, 2003).…”
Section: Background and Motivationmentioning
confidence: 99%